قراءةتحليليةنقديةلمضامين الموقع الالكترونيأرنتروبوسعنا لأنثروبولوجياالعربية - إفروجن, كهينة (Changement Social; No 03 (2017): مجــــلة التغير الاجتماعي, 2018)
تختصالأنثروبولوجيابدراسةالسلوكالإنسانيفيالماضيوالحاضر،ويقدمهذاالعلمتراكمامعرفياعنحياةالبشرعلىمرالتاريخ،وهويعتمدبذلكعلىالعلومالبيولوجيةوالاجتماعيةبالإضافةإلىالعلومالأخرى. وثمةبعضالباحثين (الأكاديميين) العربيشيرونإلىأنالأنثروبولوجيادخلتإلىالعالمالعربيتحتاسمعلمالاجتماعالمقارن،فالأنثروبولوجياكعلممستقللهميدانهومنهجهولهطريقتهالخاصة،استفادكثيرامنأدواتالجيلالثانيللويب،وتظهرهذهالاستفادةمنخلالمساهمةبعضالباحثينالعربفيإنشاءمدوناتومواقعالكترونيةتتناولعلمالأنثروبولوجيامنعدةزواياوجوانب،ويعدموقعأرنتروبوسالموقعالعربيالأولفيالأنثروبولوجيا،وعليهفانتحليلودراسةمضامينالموقعستضفيهذاالعلموالقائمينعليهفائدةمعرفيةوعلميةوفيالوقتنفسهتكشفعننقاطالنقصالتيتتخللمضامينالموقعمنذنشأتهإلىاليومالحالي،والعملعلىتقديمتقويميكونفي خدمةكلالمهتمينبعلمالأنثروبولوجيا. Anthropologyspecializes in the study of humanbehavior in the past and present, and this science provides an accumulation of knowledge for human life throughouthistory, and thereforedepends on the biological and social sciences in addition to others Sciences, and there are Arabscholarsemphasizethatanthropology has entered the Arab world under the name of comparative sociology, anthropology as an independent science has itsdomain and itsapproach and itsspecialway to Greatlybenefitsfrom the second generation of the web, and thisadvantageisdistinguished by the contribution of someArabresearchers in the creation of blogs and websitesdealingwithanthropologyfromseveral angles and aspects, and the site Arnatroposconsidersitself the first Arabic site in anthropology, and therefore the analysis and study of the content of the site willadd to this science and thosewho support itProvideuseful and scientificknowledge and at the same time reveal the missing points thatpermeate the content of the site fromitscreation to the presentday and provide an evaluationthatwill serve the people interested in the science of anthropology